Sibawayhi: By Michael G. Carter (American Journal of Islam and Society, 2006)
London and New York: I.B. Tauris and Oxford University Press India, inassociation with the Oxford Centre for Islamic Studies, 2004. 159 pages.In the “Foreword,” Michael Carter states that his book is aimed at the generalreader who is interested in the history of Arabic grammar and, in particular,in the achievement of Sibawayhi, the discipline’s architect and originator. This much-needed and long-awaited effort is a welcome addition to thefield of Arabic grammatical theory, for it contextualizes Sibawayhi’s grammaticalideas, as set forth in his Al-Kitab, by giving a short account of hisbackground and life (p. vii). The reader, whether advanced or novice, willappreciate how accessible the material has been made. To be sure, reducingSibawayhi’s complex and profound observations to 145 pages runs the riskof making it even harder to understand. But the author avoids such pitfallswith ease and grace. In fact, a knowledge of Arabic is not essential; but, asthe author says, “given the nature of the topic it will certainly be useful” (p.vii). All examples are transliterated and translated, and technical terms andbasic concepts are explained as often as possible.Despite the complex subject matter, Carter does a brilliant job describingthe Kitab’s place within the Arabo-Islamic system and the historical contextin which it was written. It is useful to spend some time on Sibawayhi’slife, even though little is actually known about it, and so chapter 1, “Sibawayhithe Person,” explores his importance through portraits in biographiesas well as from the contents of his own work. It has been convincinglyargued that the earliest form of Sibawayhi’s name (Amr ibn `Uthman Sibawayhi)is probably authentic (p. 9). That Sibawayhi was by origin a Persianwho ended up in Basra seems to be beyond contention, although neither thedate nor the place of his birth can be confirmed. All biographies agree thathe came to Basra to study religious law, either Hadith (traditions of theProphet) or basic principles of fiqh (jurisprudence), which were just beginningto take form. The details of his death are just as vague as those of hisbirth and personal history. Carter presents his readers with a short account ofthis problem, with which even the classical biographers had to wrestle (seepp. 15-16) ...